PEMBUATAN SUVENIR DENGAN TEKNIK RESIN SEBAGAI UPAYA PEMBERDAYAAN PEMUDA SELO BOYOLALI DALAM MEMBIDIK PARIWISATA - Agus Ahmadi (Institut Seni Indonesia Surakarta, 2016)
Making souvenir by resin technique is chosen within PKM (social service) program because it isunknown at Selo, and easily to do in busy time of youths. Furthermore, it is expected will developand be income source of local society. For this reason, PKM team selects two art groups which willreceive meaningful training and assistance to improve their economic income and revive localtourism object. This PKM aimed to: 1) give a discourse about making souvenir by resin technique,2) introduce and give training about alternative souvenir design, 3) give assistance about makingof model, silicon mold and foundry by resin technique. The method which used is training andassistance. The sequence of activities are preparing module, make coordination with trainees,preparing material and equipment, design souvenir, making model, training and assistance formaking souvenir by resin technique. Training and assistance of PKM conducted in three meetingswith youth organization called Gebyok and three meetings with youth organization called Samiran.Both of them have good participation, enthusiastic and orderly when join the program frombeginning to end. The results of program are: 1) trainees know about souvenir, 2) trainees knowabout material and equipment for making souvenir by resin technique, 3) trainees know aboutfundamental process for making souvenir by resin technique, 4) trainees can make and producesouvenir by resin technique such as: a) key hook with â€œkuda kepang danceâ€ relief, â€œtopengâ€ reliefand transparent resin with puppet photograph; b) â€œJarang Kepang 1 and 2â€ relief for wall ornament;c) trainees can mold by resin technique with three small sculptures in â€œcatâ€, â€œgirlâ€, and â€œbrideâ€model.Key words : resin, souvenir, silicon, and training.